Illness and health satisfaction: The role of relative comparisons - Lars Thiel (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper investigates the role of relative comparisons in health status for individual health satisfaction. Previous research stresses the importance of interdependencies in subjective well-being and health arising from positional preferences and status e ects, social health norms, and comparison processes. Using representative longitudinal data from a German population survey, we estimate empirical health satisfaction models that take these interrelations into account. We find that positional preferences and social status effects in the context of health are rather unimportant for individual health satisfaction. Furthermore, higher levels of reference-group illness can temporarily alleviate the adverse impact of one's own illness on health satisfaction. This is also the first study to show the relevance of health-related upward and downward comparisons for health perception in the general population. The results suggest that upward comparisons are more important than downward comparisons and that becoming sicker than the reference group worsens health satisfaction.
Keywords: D03; I10; 330; health satisfaction; physical illness; social status; social norms; social comparisons